Between Dream and Inherited Trauma: A Post-memory Reading of Dostoevsky's White Nights - Suryaningrum, Dyah; Atmaja, Theodore Alexander (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This article explores Fyodor Dostoevsky’s White Nights through the lens of Marianne Hirsch’s concept of post-memory, revealing how inherited trauma and societal alienation shape the novella’s protagonist. Set in 19th-century St. Petersburg, a city emblematic of Russia’s conflicting forces of modernization and tradition, White Nights presents a narrator isolated both by his introspective nature and by broader social conditions. Through a post-memory perspective, this analysis investigates the protagonist’s emotional detachment, romantic idealization, and eventual disillusionment, linking them to generational trauma and the archetype of the Russian “superfluous man.” The protagonist’s unrequited love for Nastenka is not merely a romantic fixation but a symptom of his inherited emotional burdens, reflecting how individuals inherit unresolved traumas and memories from previous generations, which shape their identities and interactions. The article further examines Dostoevsky’s critical portrayal of the Romantic “dreamer,” contrasting idealism with the grim realities of the city’s alienated inhabitants. Ultimately, this reading of White Nights highlights the novella’s enduring relevance, as Dostoevsky probes the complexities of memory, trauma, and the individual’s place within society, resonating with modern themes of inherited psychological and social dislocation.